FACTORS IN THE DECISION TO ACCEPT THE COVID-19 VACCINATION: A LITERATURE REVIEW - Astarini, Made Indra Ayu; Lilyana, Maria Theresia Arie (Nurse and Holistic Care, 2022)
Background: The COVID-19 vaccination program was an effort made to prevent the transmission of the COVID-19 virus. Various considerations arise when this program was implemented. Individual factors are one of the factors that influence the decision to receive a COVID-19 vaccination. Objective: This literature review aims to review the factors related to the decision to receive the COVID-19 vaccination. Methods: The design used was literature review with PICO criteria (Population: General public (adult), Intervention: there no Intervention just to know the correlation, Comparison: there no comparison, Outcome: factor that correlate with decision to accept COVID-19 vaccination. Other criteria is the method: quantitative study) The keywords in two languages. The keywords for articles in Indonesian are "vaksin covid-19", "keputusan", "menerima", "masyarakat", "faktor". The keywords for English articles are “Factor”, “Acceptence”, “Decision”, “Covid-19 vaccination”, “Community”. There was conducted through two databases, including: Google Scholar (479 articles in Indonesia), and Science Direct (217 articles).   Articles limited from January 2020 to Mei 2022. Then the author re-sorted the articles according were free access and full text, in the form of original articles. Results: There are 10 articles that appropriate with the criteria. Those articles are quantitative studies with a cross sectional approach. Based on the results of the article review, the authors found that there were factors related to the decision to receive the COVID-19 vaccination, namely knowledge, information about COVID-19, perception, education level, income, age, gender, and previous flu vaccine experience. Conclusion: Factors related to the decision to receive COVID-19 vaccination, namely knowledge, information about COVID-19, perception, education level, income, age, gender, previous flu vaccine experience, and history of illness. These factors can be the basis for the government to achieve successful COVID-19 vaccination achievements.